Size-dependent effect of cystine/citric acid-capped confeito-like gold nanoparticles on cellular uptake and photothermal cancer therapy - Saw, Wen Shang; Ujihara, Masaki; Chong, Wu Yi; Voon, Siew Hui; Imae, Toyoko; Kiew, Lik Voon; Lee, Hong Boon; Sim, Kae Shin; Chung, Lip Yong (Elsevier, 2018)
Physiochemical changes, including size, are known to affect gold nanoparticle cellular internalization and treatment efficacy. Here, we report the effect of four sizes of cystine/citric acid-coated confeito-like gold nanoparticles (confeito-AuNPs) (30, 60, 80 and 100 nm) on cellular uptake, intracellular localization and photothermal anticancer treatment efficiency in MDA-MB231 breast cancer cells. Cellular uptake is size dependent with the smallest size of confeito-AuNPs (30 nm) having the highest cellular internalization via clathrin- and caveolae-mediated endocytosis. However, the other three sizes (60, 80 and 100 nm) utilize clathrin-mediated endocytosis for cellular uptake. The intracellular localization of confeito-AuNPs is related to their endocytosis mechanism, where all sizes of confeito-AuNPs were localized highly in the lysosome and mitochondria, while confeito-AuNPs (30 nm) gave the highest localization in the endoplasmic reticulum. Similarly, a size-dependent trend was also observed in in vitro photothermal treatment experiments, with the smallest confeito-AuNPs (30 nm) giving the highest cell killing rate, whereas the largest size of confeito-AuNPs (100 nm) displayed the lowest photothermal efficacy. Its desirable physicochemical characteristics, biocompatible nature and better photothermal efficacy will form the basis for further development of multifunctional confeito-AuNP-based nanotherapeutic applications.